Pengaruh Promosi, Kualitas Pelayanan dan Suasana Toko Terhadap Keputusan Pembelian (Studi pada Konsumen Toko Buku Gramedia Cabang Plaza Bintaro di Tangerang Selatan) - Satrio Widhi Nugroho; Agus Sriyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine the effect of promotion, service quality and store atmosphere on purchasing decisions at the Gramedia Bookstore in Plaza Bintaro. The population in this study were consumers of the Gramedia Bookstore in Plaza Bintaro who made purchases. The sample in this study amounted to 100 respondents. The data were processed using the help of the SPSS 26 statistical analysis program and Microsoft Excel 2013. The results of the study were that promotion, service quality and store atmosphere partially had a significant effect on purchasing decisions at the Gramedia Bookstore in Plaza Bintaro.